2012
DOI: 10.1007/s10342-012-0664-z
|View full text |Cite
|
Sign up to set email alerts
|

Greater abundance of Fagus sylvatica in coniferous flood protection forests due to climate change: impact of modified root densities on infiltration

Abstract: Climate change is expected to modify the spatial distributions of zonal forest communities and thus, their species compositions. The aim of this paper was to study the impact of higher abundance of beech on water storage capacity in current coniferous flood protection forests due to varying root densities of the main tree species. Two forest communities in the northern pre-Alps in Switzerland with similar soil properties but varying in species composition were investigated (space-for-time substitution). It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
(37 reference statements)
3
12
0
Order By: Relevance
“…() found root length densities between 0.44 and 2.21 cm/cm 3 in the topsoil of a mixed Norway spruce‐Silver fir forest stand, which corresponds to the values we obtained for the 4‐month and 8‐month old alders. In our study most of the alder roots were smaller than 2 mm in diameter, confirming the importance of the role of fine roots and mesopores (0.5–2 mm in diameter; Sidle et al ., ; Lange et al ., ) and even of root hairs (Bengough, ) in preferential flow paths and saturated flow.…”
Section: Discussionmentioning
confidence: 97%
“…() found root length densities between 0.44 and 2.21 cm/cm 3 in the topsoil of a mixed Norway spruce‐Silver fir forest stand, which corresponds to the values we obtained for the 4‐month and 8‐month old alders. In our study most of the alder roots were smaller than 2 mm in diameter, confirming the importance of the role of fine roots and mesopores (0.5–2 mm in diameter; Sidle et al ., ; Lange et al ., ) and even of root hairs (Bengough, ) in preferential flow paths and saturated flow.…”
Section: Discussionmentioning
confidence: 97%
“…The spatial distributions of roots is linked to the distribution of unit area of momentum dissipation per unit volume L through empirical relationships. The results of previous studies suggest a plausible relation between these two parameters (Lange et al, 2012). The estimated spatial distribution of L implemented in the W 2 model quantifies the hydrological connectivity of vegetated hillslopes of various forest structures and soil conditions ( Fig.…”
mentioning
confidence: 76%
“…Previous studies (Lange et al, 2012) have shown that vertical preferential flow in rooted soils can be quantified at the soil profile scale using a dual porosity models (Šimůnek et al, 2003). In this work we combine the Stokes flow approach (Beven and Germann, 2013) for vertical and lateral fluxes, and the mass balance equation in order to couple information about root distribution, variation of soil water content, and runoff behaviors.…”
Section: Preferential Flow Modeling At the Soil Profile Scalementioning
confidence: 99%
See 1 more Smart Citation
“…according to many authors, natural forests with complexity and integrity are able to withstand various stresses (Dhôte, 1994;Holling, 2001;smith, 2001;Bréda et al, 2006;Weber et al, 2007;Galiano et al, 2010;lloret et al, 2011Cheaib et al, 2012;lange et al, 2012;Michelot et al, 2012;Cavin et al, 2013;vilá-Cabrera, 2013;Morán-lopéz et al, 2014;lawson et al, 2015;Merlin et al, 2015;pötzelsberger et al, 2015) and they are not severely prone to negative functional climate change effects, and therefore, key forest functions can be maintained.…”
Section: Methodsmentioning
confidence: 99%